Bolton tooth size discrepancy among different malocclusion groups in two different ethnic groups of Nepalese population (Orthodontic Journal of Nepal, 2021)
Introduction: The tooth size ratios may vary among different ethnic groups and different malocclusion groups. The objective of this study is to see the tooth size discrepancies in two major ethnic groups of Nepal; Indo-Aryans and Tibeto-Burmans and different malocclusion groups and compare it with the Bolton’s study.Materials and Method: The anterior and overall ratios were compared between Indo-Aryans and Tibeto-Burmans according to different malocclusion groups with Bolton’s study with one sample t-test. The differences in ratios in ethnic groups and gender were seen with one sample t-test. The differences in mesio-distal tooth width amongst the two ethnic groups were seen. One sample ANOVA was used to see any correlation between the ethnic groups and the different malocclusion groups.Result: The anterior ratio and overall ratio in Indo- Aryans and Tibeto-Burmans in all the malocclusion groups were greater than the Bolton’s study but was not statistically significant. There was significant differences in anterior ratio between Indo-Aryans (77.63 + 2.74%) and Tibeto-Burmans (78.51 + 2.76%), p value= 0.024. There were no statistical significant differences in the anterior and overall ratio amongst males and females. The mesio-distal tooth size was greater in Tibeto-Burmans as compared to Indo-Aryans expect for maxillary right and left central incisors.Conclusion: The Tibeto-Burmans had higher anterior ratio as compared to Indo-Aryans. The Tibeto-Burmans had broader teeth as compared to Indo-Aryans except for maxillary central incisors.